26 Law enforcement-involved deaths in illinois 2005–2010 –demographics and circumstances regarding initiation of contact. (19th September 2017) - Mason, Maryann; McLone, Suzanne; Snow, Lisa; Jones, Mark; Sheehan, Karen
Abstract : Statement of Purpose: To report demographics and selected circumstances surrounding law enforcement-involved deaths in five Illinois counties from 2005–2010. Methods/approach: Data come from the Illinois Violent Death Reporting System (IVDRS) which collects information from death certificates, coroner/medical examiner, and law enforcement reports. Cases identified as law enforcement deaths occurring between 2005 and 2010 were pulled from the IVDRS. Cases were analysed using descriptive methods for decedent age, race/ethnicity, toxicology, and weapon type. Narrative statements summarising details of each incident were analysed using qualitative methods, focusing on the circumstances regarding the initiation of contact between law enforcement and the decedent. Thematic categories fitting the data were developed from data using inductive methods. Results/Conclusions: 129 cases meeting study criteria were identified. The majority of incidents (68.5%) involved Black decedents, median decedent age was 27 years old. Most (96.8%) of these incidents involved firearms and all of the 52.7% of incidents with recorded firearm type involved handguns. Nearly half (44.4%) of decedents tested positive for alcohol, 44.4% tested positive for cocaine, 4.1% tested positive for opiates. We identified three broad categories regarding contact initiation between law enforcement and decedents: 1) calls for service for a crime in progress excluding self-harm/domestic violence, 2) calls for domestic violence/self-harm and 3) officer initiated contacts (traffic stops, suspected suspicious activity). Significance and Contributions to Injury and Violence Prevention Science: While there is some emerging data about the demographics of decedents in law enforcement deaths, there are no studies we are aware of that use surveillance data to identify patterns in circumstances surrounding the initiation of incidents resulting in law enforcement deaths. These study findings contribute to improved understanding of the circumstances associated with the initiation of incidents and can inform efforts to prevent law enforcement deaths.